A review of the neuroscience of religion: an overview of the field, its limitations, and future interventions - Carvour, Harrison M.; Radke, Anna K.; French, Nathan S. (Frontiers in Neuroscience, 2025)
The neuroscience of religion (NoR), a field that studies various neural mechanisms and functions alongside their correlational relationships with religious phenomena, holds immense potential for development. Standard research methods, including brain imaging techniques and lesion studies, establish relationships between brain functions and religious practices, beliefs, and experiences. Despite increasing interest in this field since the start of the century, NoR has many limitations regarding the technology presently used, particularly in investigating specific aspects of religious behaviors regarding ritualized movements. However, using technologies not presently used in the field, such as functional near-infrared spectroscopy (fNIRS), along with applying other religious theories, could allow researchers to examine other behaviors, expand their understanding of religion, and bypass current limitations. Therefore, this review paper critically examines NoR, including discussions on methodologies and conclusions from the field, the application of theories of religion currently used, limitations of research methods, the potential incorporation of other theories of religion in the future, and the utilization of other technologies not presently employed in the field, possibly opening new avenues for inquiry and analysis.